PEMILIHAN PUSAT KEGIATAN LOKAL DI KABUPATEN KETAPANG PROPINSI KALIMANTAN BARAT - B61110057, RULLY OKTARIADHY (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT This study aims to select the territories District in Ketapang that should be used as centers of local economic growth and establishing zones Local Activities Center (PKL) in Ketapang in West Kalimantan. Ketapang is one district that were taken into account in the system of national and regional spatial layout system in West Kalimantan and has several important positions in the status Ketapang district in regional. Centers of economic growth in Ketapang expected impact on improving equity in the welfare of the people through development. To achieve these goals one in the travel path is to choose the centers of economic growth in Ketapang that will accelerate the growth of the surrounding areas. The analytical tool used in the study is Scalogram Analysis, Analysis of Interaction or Gravity, Focus Group Discussion (FGD) and Approach Advantages Agglomeration. The results showed that in Ketapang has a center of economic growth in the District Delta Pawan as a Regional Activity Center (PKW) and the District Kendawangan, District Manis Mata, District Simpang Sandai and Hulu as the Local Activity Center (PKL). Where the dynamics of the economy in Ketapang increasingly shifted to the Agribusiness sector. This happens due to the area and natural resources owned by the Ketapang District is very diverse.